2016
DOI: 10.1186/s12882-016-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in renal WT-1 expression preceding hypertension development

Abstract: BackgroundHypertension is a public health problem with mostly unknown causes, and where strong hereditary genetic alterations have not been fully elucidated. However, the use of experimental models has provided valuable information. Recent evidences suggest that alterations in key nephrogenic factors, such as Wilms’ tumor 1 transcription factor (WT-1), could contribute to the development of hypertension. The aim of this paper is to evaluate the expression of WT-1 and related genes in the nephrogenic process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…In the presence of ROS, cytochrome c peroxidase causes cardiolipin peroxidation and cristae degradation (4). Mitochondrial health is important for podocyte function, actin assembly (1), and protection from apoptosis (23) as well as for expression and trafficking of nephrin and WT1 (24,32). In our study, morphological analysis indicated structural damage to podocyte mitochondria in MetS, and cardiolipin colocalized well with WT1 staining, implicating mitochondrial injury in the podocyte pathology associated with MetS.…”
Section: Discussionsupporting
confidence: 52%
“…In the presence of ROS, cytochrome c peroxidase causes cardiolipin peroxidation and cristae degradation (4). Mitochondrial health is important for podocyte function, actin assembly (1), and protection from apoptosis (23) as well as for expression and trafficking of nephrin and WT1 (24,32). In our study, morphological analysis indicated structural damage to podocyte mitochondria in MetS, and cardiolipin colocalized well with WT1 staining, implicating mitochondrial injury in the podocyte pathology associated with MetS.…”
Section: Discussionsupporting
confidence: 52%
“…In this regard, we recently showed that changes in the expression pattern of the WT-1 transcription factor, a key mediator of nephrogenesis, could contribute to anatomical and functional kidney disorders linked to hypertension development. These changes could respond to VDR modulation ( Figure 1) [Mazzei et al 2016].…”
Section: Vdr Effects Unrelated To Calciumphosphorus Metabolismmentioning
confidence: 99%
“…Membrane fractions were prepared as previously described. 8 The supernatant was separated and again centrifuged, this time at 19 500 rpm, and the protein concentration of the membrane fraction lysate was quantified by the Lowry assay using bovine serum albumin as a standard. A sample (40 μL) of the membrane fraction resuspended in lysis buffer was rapidly read using a spectrofluorometer (FluoroCount; AF10001, Cambers) to establish the basal value of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, renal expression of WT-1 during the organogenesis process is modulated by oxidative/ inflammatory alterations, and phenotypic alteration of WT-1, either in its expression and/or location, produces pathological states both at the vascular and renal levels. 8 In this regard, a suitable animal model for studying the pathophysiological processes associated with vascular dysfunction may be the spontaneously hypercholesterolemic apolipoprotein E knockout (ApoE-KO) mouse. A major function of ApoE is to transport lipids among various cells and tissues of the body, and as a constituent of high density lipoproteins (HDL) is involved in cholesterol homeostasis and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation